FINITE ELEMENT STRESS AND STRAIN ANALYSIS OF BGA SOLDER JOINT OF BOARD LEVEL OPTICAL INTERCONNECTION MODULE UNDER TEMPERATURE AND VIBRATION COUPLED CONDITION - HUA JianWei; HUANG ChunYue; LIANG Ying; HUANG Wei; ZHANG Long (Jixie qiangdu)
Based on ANSYS software established board level optical interconnect module finite element model,by means of the analysis of the model of the thermal-structure random vibration coupling,obtained the data of stress and strain under the coupling condition,analyzed the influence of the change of the shape parameters of three kinds of solder joints,the height of the solder joints,the diameter of the pad and the volume of the solder balls.The results show that the stress and strain value of the solder joint is gradually reduced from the center position to the solder joint at both ends;the maximum stress and strain point appeared in the solder joint at the corner of the array.With the increase of the solder joint height,the maximum stress and strain of the solder joint increased gradually.With the increase of the diameter of the pad and the volume of the solder ball,the maximum stress and strain decreased gradually.